Mortality pattern of Karan Fries males in an organized herd - panmei, achun; Gupta, A. K.; Shivahre, P. R. (Indian Journal of Dairy Science, 2014)
Mortality pattern analysis of breeding males is very useful to develop effective breeding and management strategies for enhancing intensity of selection among males required for inclusion in test mating in the progeny testing programme. Records of 16 years from 1997-2012 maintained at ABRC, NDRI Karnal were collected to examine the mortality pattern in different age group of KF (Holstein Friesian crossbred) males across different period of birth, season of birth, and genetic groups in NDRI herd. The results showed that respiratory problems (3.33%) and enteritis (1.82%) were the main causes of mortality in 0-1mo and 1-2mo age groups, respectively whereas general debility was the main cause of mortality in 2-3mo (1.42%), 3-6mo (2.14%) and 6-18mo (4.86%) age groups. In age group of 18mo-3yrs, respiratory problems (0.52%) and above 3 years of age, respiratory problems (2.07%) were the main causes of mortality. Mortality was observed to be maximum in males born in the period P-4 (44.76%) followed by P-1 (30.84%), P-3 (24.31%) and P-2 (19.57%). The results showed that mortality percent was the highest in male calves born in summer (33.57%) and autumn (33.06%) seasons than those born in winter (31.03%) and rainy (4.66%) seasons for most of the different age groups. The lowest mortality was observed in F1 males (16.67%) as compared to KF crosses which had higher exotic inheritance G-2 (29.09%) and G-3 (35.19%). Overall, the findings revealed high mortality rate in KF males in younger age groups, higher exotic inheritance genetic groups and male calves born in P-4 as well as summer seasons hence suggesting the need of intensive health care and management conditions to be provided to the young males to minimize the mortality and increase the economic return.